Tool wear analysis in end milling of advanced ceramics with TiAlN and TiN coated carbide inserts - Reddy, M. Mohan; Gorin, Alexander; Abou-El-Hossein, Khaled; Debnath, Sujan; Ali, Mohammad Yeakub; Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2012)
Advanced ceramic materials are difficult to machine by conventional methods due to the brittle nature and high hardness. The appropriate selection of cutting tool and cutting conditions may help to improve machinability by endmilling. Performance of TiAlN and TiN coated carbide tool insert in end milling of machinable glass ceramic has been investigated. Several dry cutting tests were performed to select the optimum cutting parameters for the endmilling in order to obtain better tool life. In this work, a study was carried out on the influence of cutting speed, feed rate and axial depth of cut on tool wear.The technique of design of experiments (DOE) was used for the planning and analysis of the experiments. Tool wear prediction model was developed using Response surface methodology.The results indicate that tool wear increased with increasing the cutting speed and axial depth of cut. Effect of feed rate is not much significant on selected range of cutting condition